Environmental Utilization as Learning Resource by Geography Teacher to Apply Religius Characteristic in Public High School (SMAN) Lombok Timur - Apriani, Rezita; Rahmanelli, Rahmanelli (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
This study is purposed to obtain objective data about environmental availability as a learning source and its relevance to Core Competency (KI) and Basic Competency (KD) of public senior high school (SMAN) in East Lombok; the use of environment as a learning source by geography teachers to shape religious characters and to know teacher barriers in using environment as a learning source, and also to determine priority of directive policy in utilizing environment as a learning source in geography subject at SMAN East Lombok. Type of research was qualitative research. Data were collected through observation, interview, and documentation. Data analysis consisted of data reduction, data presentation, verification, and ISM (Interpretative Structural Modeling). This study found out that: (1) in aspect of environmental availability as a learning source, physical and non physical environment are available to be used as a learning resource and it is relevant to KI and KD in SMAN East Lombok. (2) In utilization aspect, the form of physical and non physical utilization in religious characteristic application at school has been exploited by geography teacher to form religious character. However, environmental utilization outside the school is not optimal, because of the obstacles. (3) Constraints that teacher encounter are to coordinate students, infrastructure, to make plan, to understand parties that involved such as parent and family consent, to analyze the availability in the development of learning resources. (4) Policy priority that arise in utilizing the environment as a source of geography learning is improving skill development of geographic teacher implementation in collaboration with other offices and schools; structural planning by geography teachers to utilize the environment as a learning source and established a committee to explore the availability; analyzing condition and availability in the development of learning resources.